Ancient Origin of Two 5S rDNA Families Dominating in the Genus Rosa and Their Behavior in the Canina-Type Meiosis - Vozárová, Radka; Herklotz, Veit; Kovařík, Aleš; Tynkevich, Yuri O.; Volkov, Roman A.; Ritz, Christiane M.; Lunerová, Jana (Frontiers in Plant Science, 2021)
The genus Rosa comprises more than 100 woody species characterized by intensive hybridization, introgression, and an overall complex evolutionary history. Besides many diploid species (2n = 2x = 14) polyploids ranging from 3x to 10x are frequently found. Here we analyzed 5S ribosomal DNA in 19 species covering two subgenera and the major sections within subg. Rosa. In addition to diploids and polyploids with regular meiosis, we focused on 5x dogroses (Rosa sect. Caninae), which exhibit an asymmetric meiosis differentiating between bivalent- and univalent-forming chromosomes. Using genomic resources, we reconstructed 5S rDNA units to reveal their phylogenetic relationships. Additionally, we designed locus-specific probes derived from intergenic spacers (IGSs) and determined the position and number of 5S rDNA families on chromosomes. Two major 5S rDNA families (termed 5S_A and 5S_B, respectively) were found at variable ratios in both diploid and polyploid species including members of the early diverging subgenera, Rosa persica and Rosa minutifolia. Within subg. Rosa species of sect. Rosa amplified the 5S_A variant only, while taxa of other sections contained both variants at variable ratios. The 5S_B family was often co-localized with 35S rDNA at the nucleolar organizer regions (NOR) chromosomes, whereas the co-localization of the 5S_A family with NOR was only exceptionally observed. The allo-pentaploid dogroses showed a distinct distribution of 5S rDNA families between bivalent- and univalent-forming chromosomes. In conclusion, two divergent 5S rDNA families dominate rose genomes. Both gene families apparently arose in the early history of the genus, already 30 myrs ago, and apparently survived numerous speciation events thereafter. These observations are consistent with a relatively slow genome turnover in the Rosa genus.